Research on Collision Detection Algorithm for Human-SRL Collaborative Motion Planning - Zhang, Xiaobo; Liu, Jinguo (Journal of physics. Conference series, 2022)
The existing collision detection algorithms are commonly based on triangle patch models, which leads to complex detection logic. Aiming at this problem, this paper proposes a new collision detection algorithm. It has simple detection logic and fast detection speed, and it is mainly used for human-SRL cooperative motion planning. The algorithm is based on a human-SRL skeleton model and a multi-sphere envelope method and includes four sub-algorithms, namely, a multi-sphere envelope sub-algorithm, an SRL collision detection sub-algorithm, a collision detection sub-algorithm between SRL and human, and a collision detection sub-algorithm between SRL and environment objects. This paper first introduces the pseudo-code of the collision detection algorithm. Secondly, the implementation principles of its four sub-algorithms are expounded. Finally, the correctness of the collision detection algorithm is verified by simulation.